2023
DOI: 10.1021/acs.joc.2c02987
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Influences on the Dynamic Range of Photoswitchable Dithienylethene–Thiourea Organocatalysts

Abstract: Thiourea-based organocatalysts bearing a photoswitchable dithienylethene (DTE) core and a wide range of substituents were prepared and extensively tested for their ability to accelerate the Michael reaction between acetylacetone and trans-β-nitrostyrene. There is a strong correlation between the Hammett parameter of the modulating groups and catalytic activity following UV irradiation. Electron-withdrawing groups afford the largest reactivity difference between the catalysts in their ring-open form and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…41,42 As expected, this result corroborates that the phosphanyl and electron-modulating groups in the non-planar structure of DTE o -COCF 3 When two equivalents of the phosphine ligands were used to react with trans-[PdCl 2 (PhCN) 2 ], monometallic palladium(II) 1:2 type complexes were formed (Figure 1a). For all these compounds, an isolated singlet was registered in their 31 P{ 1 H} NMR spectra that shifted downfield to δ ≈ 12 ppm, thereby corroborating metal complexation and the formation of exclusively one isomer (cis or trans). In addition, negligible differences were found in the chemical shift of this 31 P{ 1 H} NMR signal for the three Pd complexes prepared, which again demonstrates the lack of electronic communication between the external thiophene substituents in the open isomer of the ligands.…”
Section: Synthesis Of Photoswitchable Ligands and Monometallic Complexesmentioning
confidence: 66%
See 2 more Smart Citations
“…41,42 As expected, this result corroborates that the phosphanyl and electron-modulating groups in the non-planar structure of DTE o -COCF 3 When two equivalents of the phosphine ligands were used to react with trans-[PdCl 2 (PhCN) 2 ], monometallic palladium(II) 1:2 type complexes were formed (Figure 1a). For all these compounds, an isolated singlet was registered in their 31 P{ 1 H} NMR spectra that shifted downfield to δ ≈ 12 ppm, thereby corroborating metal complexation and the formation of exclusively one isomer (cis or trans). In addition, negligible differences were found in the chemical shift of this 31 P{ 1 H} NMR signal for the three Pd complexes prepared, which again demonstrates the lack of electronic communication between the external thiophene substituents in the open isomer of the ligands.…”
Section: Synthesis Of Photoswitchable Ligands and Monometallic Complexesmentioning
confidence: 66%
“…This behavior is characteristic of closed state DTEs, 45 as confirmed by TD-DFT calculations (Table S5, Figures S23-S25) and additional NMR spectroscopic measurements. In particular, we observed the appearance of a new set of signals for the closed isomer in the 1 H, 31 P (proton-coupled and decoupled) and, when applicable, 19 F NMR spectra of the UV-irradiated ligands in toluene-d 8 , which were upfield ( 1 H NMR) or downfield shifted ( 31 P, 31 P{ 1 H} and 19 Analysis of this NMR data also revealed that the photocyclization reaction of DTE-based ligands was not quantitative. Instead, a photostationary state (PSS) composed of an equilibrium mixture of the ligands' o and c states was obtained in all the cases, since both isomers absorb at the UV excitation wavelength used and, therefore, should simultaneously undergo ring-closing and ringopening reactions.…”
Section: Synthesis Of Photoswitchable Ligands and Monometallic Complexesmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, other electronic features that accompany DTE photoisomerization have yet to be exploited in metal-based photoswitchable catalysis. In this work, we proposed to explore one of these additional features: the variation in electronic communication between the external thiophene substituents upon photoconversion, which has already been utilized to control chemical reactivity with light-responsive organocatalysts , and organic substrates. , In particular, herein, we devised the synthesis of nonsymmetric DTE derivatives as photoswitchable ligands bearing (i) a metal-binding phosphine group at one thiophene ring and (ii) an electron-withdrawing substituent at the other (Scheme b). As these two groups must be electronically insulated in the open state of the system and become selectively conjugated upon ring-closing, our molecular design should allow modulating the electron density of the phosphine ligand with light and, eventually, the catalytic activity of metal centers upon coordination.…”
Section: Introductionmentioning
confidence: 99%